Processamento auditivo central em adultos: uma abordagem por meio de avaliações comportamentais e frequency-following response com estímulo de fala - Sanguebuche, Taissane Rodrigues (2018)
The aim of this research was to generate reference values for different behavioral tests of central auditory processing (CAP), with age stratification, and for measures of latency, amplitude, slope and interpeaks of Frequency-Following Response potential with speech stimulus (FFR-speech) in normal hearing adults. Also, to compare these results according to the variables of age and presence or absence of CAP disorder. The distribution of the groups with normality and disorder of CAP was carried out according to the performance in the Dichotic Sentence Identification test (DSI), Masking Level Difference (MLD), Randon Gap Detection Test (RGDT), Adapted Time-Compressed Speech Test (TCST) and Duration Pattern and Pitch Pattern tests (DP/PP) from Auditec®. The subjects who presented normality in all the tests make up the G1 group and the subjects with alteration in at least one of them originated the G2 group. Therefore, the casuistry was composed of 94 subjects, at least 11 years of schooling, being 64 participants of the G1 and 30 of the G2. To generate the reference values, a sum of the mean performance of the G1 group at two standard deviations, already predicting the possible variability of the responses among the subjects. For CAP tests, the general age group was divided into two groups, from 18 to 29 years and from 30 to 58 years, taking into account the maturation of the auditory pathway. The performance in the behavioral tests was very similar in both age groups. When comparing the G1 and G2 groups, there was significant difference in the DSI (left ear), MLD, RGDT, DP and PP to the group aged between 18 and 29 years and, DSI (right ear) to the group from 30 to 58 years, with worse results in the altered group. For the electrophysiological evaluation, age fractionation was not performed, as suggested by a well-known study of the area, which showed stability in the neural response of adults. The values found as reference remained, in general, similar to the researched literature. When comparing the groups, the G2 presented increased latencies for the C and O waves in relation to the G1, which was not found in the other analysis carried out.